Introduction to organic and medicinal chemistry - Keighley, Nathan (Boca Raton, FL : CRC Press, 2025)
"This text is designed to be an undergraduate reference textbook for students of chemistry who aim to select degree modules geared towards medicinal chemistry. In the first two chapters, it offers an overview of basic organic chemistry, followed by organic synthesis in chapter 3, with an emphasis on the importance of synthetic procedures in relation to the chemistry of drug design. In Chapter 4, the book covers foundational aspects of biochemistry and biomedical science to provide a basis for students understanding where and how drugs work on selected targets. Later, the book explains how medicines have been created for selected topics in medicinal chemistry - namely against pathogens, cancer, and neurological targets"--
Includes bibliographical references and index.
Keywords: Pharmaceutical chemistry -- Textbooks; Chemistry, Organic -- Textbooks